2012
DOI: 10.1038/onc.2011.654
|View full text |Cite
|
Sign up to set email alerts
|

Established and new mouse models reveal E2f1 and Cdk2 dependency of retinoblastoma, and expose effective strategies to block tumor initiation

Abstract: RB +/− individuals develop retinoblastoma and, subsequently, many other tumors. The Rb relatives p107 and p130 protect the tumor-resistant Rb−/− mouse retina. Determining the mechanism underlying this tumor suppressor function may expose novel strategies to block Rb-pathway cancers. p107/p130 are best known as E2f inhibitors, but here we implicate E2f-independent Cdk2 inhibition as the critical p107 tumor suppressor function in vivo. Like p107 loss, deleting p27 or inactivating its Cdk inhibitor (CKI) function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 52 publications
5
60
0
Order By: Relevance
“…Second, the spacer domain of p107 (but not Rb) acts as a CDK2 inhibitor [36]. Indeed, deletion of p107 has a similar effect as deletion of the CDK inhibitor p27 on retinoblastoma formation in murine models [37]. Deletion of Rb and p107 in some contexts leads to enhanced proliferation and cancer such as retinoblastoma in mice, but may also lead to more severe differentiation defects in muscle [38] or, as shown here, to increased apoptosis in pancreatic islet cells.…”
Section: Discussionmentioning
confidence: 74%
“…Second, the spacer domain of p107 (but not Rb) acts as a CDK2 inhibitor [36]. Indeed, deletion of p107 has a similar effect as deletion of the CDK inhibitor p27 on retinoblastoma formation in murine models [37]. Deletion of Rb and p107 in some contexts leads to enhanced proliferation and cancer such as retinoblastoma in mice, but may also lead to more severe differentiation defects in muscle [38] or, as shown here, to increased apoptosis in pancreatic islet cells.…”
Section: Discussionmentioning
confidence: 74%
“…A number of studies support the classical model that high E2F and Cdk activity explains the increased proliferation of RB mutant cells (Tsai et al 1998;Chong et al 2009;Sangwan et al 2012), but this idea has not been systematically studied in vivo. Similarly, the death of some progenitors when they are induced to differentiate in the absence of RB is probably in large part dependent on the p53 axis, but this has not been thoroughly investigated.…”
Section: Liver Oval Cellsmentioning
confidence: 79%
“…Inactivation of the E2f1-3 genes in mouse retinal progenitors further showed that these E2F factors, the activity of which is increased in the absence of RB, play a critical role in the survival of these progenitors-and not, surprisingly, in their capacity to proliferate Chong et al 2009). In Rbdeficient retinal progenitors, removal of only one allele of the E2f1 gene is sufficient to prevent tumor initiation; furthermore, blockade of Cdk2 activity during a short period of time in young mice is sufficient to prevent retinoblastoma development (Sangwan et al 2012). Thus, the expansion of Rb mutant retinal progenitors is dependent on increased E2F and Cdk2 activity.…”
Section: Retinal Progenitorsmentioning
confidence: 97%
“…A key goal in the immediate future will be to identify the consequences of RB1 inactivation that can be best exploited therapeutically to target RB1 mutant tumors. little progress has been reported on this subject, and only a few compounds have been available for research (Ma et al 2008;Sangwan et al 2012;Kurtyka et al 2014).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…The current models of RB function predict that the uncontrolled cell proliferation of RB1 mutant cells is driven by deregulated E2F. Remarkably, studies using mouse models of retinoblastoma have shown that the short-term exposure of fetuses to E2F or CDK inhibitors is sufficient to suppress tumor formation in long-term assays (Sangwan et al 2012). One might imagine that effective inhibitors of E2F activation would be high on the wish list of many pharmaceutical companies, but, to date, very Figure 4.…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%